ASSESSMENT OF FIREFIGHTING FACILITIES AND ROADS REGARDING WITH FIRE-RESISTANT FOREST PROJECT (YARDOP) - Bilici, Ebru; Gencal, Burhan; Taş, İnanç; Akay, Abdullah Emin (EDITURA UNIV, 2019)
As a result of natural disasters such as fire, storms, avalanches etc., natural resources have been destroying rapidly in the world. Due to global warming and other factors, forest fires result in serious damages on forest resources in arid regions. Therefore, firefighting activities should be well planned and special attention should be paid to grow fire-resistant forest in the regions with high fire risk. For this purpose, firefighting facilities (i.e. fire breaks, fire lines) and roads for the purpose of fire protection and fire-fighting should be specially evaluated in these regions. Road networks are effectively used during and after a fire and are also used to stop the fire. In this study, the firefighting facilities and roads developed for fire intervention within the Fire- Resistant Forest Project (YARDOP) have been evaluated. Within the project, firefighting facilities have been planned to build a fire-resistant stands. These firefighting facilities can also be used for firefighting purposes. This study indicated that the standards of firefighting facilities and roads used in YARDOP projects are likely to be an alternative solution for many countries, especially in the Mediterranean countries and generally in the same environmental conditions around the world.
Keywords: forest fires; forest roads; fire breaks and fire lines; YARDOP